Queering Mennonite Literature - Cruz, Daniel Shank (Penn State University Press, 2025)
Though the terms “queer” and “Mennonite” rarely come into theoretical or cultural contact, over the last several decades writers and scholars in the United States and Canada have built a body of queer Mennonite literature that shifts these identities into conversation. In this volume, Daniel Shank Cruz brings this growing genre into a critical focus, bridging the gaps between queer theory, literary criticism, and Mennonite literature.